2020
DOI: 10.3390/agronomy10010135
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Flowering Time and Tillering on Grain Yield of Sorghum Hybrids across Diverse Environments

Abstract: Sorghum in Australia is grown in water-limited environments of varying extent, generating substantial genotype × environment interactions (GEIs) for grain yield. Much of the yield variation and GEI results from variations in flowering time and tillering through their effects on canopy development. The confounding effects of flowering and tillering complicate the interpretation of breeding trials. In this study, we evaluated the impacts of both flowering time (DTF) and tillering capacity (FTN) on the yield of 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This result is supported by the studies of Olukolu et al [48] and Gbaguidi et al [49]. Various studies have shown the GEI effect on several crops such as cassava [50], rice [51,52], sweet potato [53], and sorghum [54]. Yan and Kang [19] stated that the number of genotypes and environments determines the extent of environmental variation.…”
Section: Gge Biplot Analysismentioning
confidence: 63%
“…This result is supported by the studies of Olukolu et al [48] and Gbaguidi et al [49]. Various studies have shown the GEI effect on several crops such as cassava [50], rice [51,52], sweet potato [53], and sorghum [54]. Yan and Kang [19] stated that the number of genotypes and environments determines the extent of environmental variation.…”
Section: Gge Biplot Analysismentioning
confidence: 63%
“…Originating from tropical and subtropical regions of Africa and later Southeast Asia, this climate resilient, C4 crop can now also be found in temperate growing regions of Australia, Europe and the Americas 1 – 3 . The grain is a popular gluten free substitute, the stalks are juiced for syrup in ethanol production and biomass is used as forage 4 6 . Lignocellulosic biomass from bioenergy sorghums are promising feedstocks for production in areas with marginal fertility 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Present study found that water deficit conditions could stimulate the formation of more unproductive tiller rather than normal irrigated conditions, in both varieties. The higher rate of unproductive tillers formation could lead to a decrease in crop yield (Fioreze et al 2020;Wang et al 2020).…”
Section: Discussionmentioning
confidence: 99%